2017
DOI: 10.1016/j.socscimed.2016.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood age structure and cognitive function in a nationally-representative sample of older adults in the U.S.

Abstract: Recent evidence suggests that living in a neighborhood with a greater percentage of older adults is associated with better individual health, including lower depression, better self-rated health, and a decreased risk of overall mortality. However, much of the work to date suffers from four limitations. First, none of the U.S.-based studies examine the association at the national level. Second, no studies have examined three important hypothesized mechanisms - neighborhood socioeconomic status and neighborhood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 51 publications
(86 reference statements)
3
16
1
Order By: Relevance
“…The association between proportion of people aged 60 years or older and reduced risk of incident dementia is in agreement with a recent study showing that living in a neighborhood with a higher percentage of older people (≥65 years) is related to better individual cognition at baseline [35]. This is in accordance with the hypothesis that living in these neighborhoods may be more suitable for older people (responsive services, better social interactions...) [36,37].…”
Section: Discussionsupporting
confidence: 91%
“…The association between proportion of people aged 60 years or older and reduced risk of incident dementia is in agreement with a recent study showing that living in a neighborhood with a higher percentage of older people (≥65 years) is related to better individual cognition at baseline [35]. This is in accordance with the hypothesis that living in these neighborhoods may be more suitable for older people (responsive services, better social interactions...) [36,37].…”
Section: Discussionsupporting
confidence: 91%
“…Education and social engagement are well-established protective factors for cognitive health in ageing (37), and previous studies have shown that urban-rural variations in cognitive functioning could be ascribed to differences in mental stimulation received through education (16) or through social engagement (38). However, the interactions remained significant even after controlling for educational attainment or social engagement in our multivariate models, suggesting that socioeconomic circumstances did not fully account for the association between neighbourhood urbanity and disabilities in our sample.…”
Section: Accepted Manuscriptcontrasting
confidence: 56%
“…1 Existing studies have noted that self-neglect in older adults is frequently pathological in nature, with individuals with dementia, frontal lobe dysfunction, and depression often neglecting personal hygiene and living in unsanitary conditions. 5 The authors' findings thereby expand upon literature indicating the importance of social cohesion in reducing risk of cognitive decline and improving mental well-being, creating an additional connection to selfneglect. 5,6 Because the effect of neighborhood cohesion may be especially potent in immigrant communities, to understand the relationship between neighborhood cohesion and self-neglect better, future studies should examine the effect of social cohesion on cognitive decline specifically in Chinese-American immigrant older adults.…”
supporting
confidence: 55%